Distribusi Biomassa dan Karbon Tingkat Semai Jenis Manggis, Lengkeng, Sengon dan Jelutung: Seed-Level Biomass and Carbon Distribution Types of Mangosteen, Longan, Sengon and Jelutung - Yetrie Ludang; Wahyu Supriyati; Alpian Alpian (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
The carbon content in trees is affected by the amount of tree biomass. The value of the biomass content of the tree indicate to the value the carbon content. It is interest to study of the growth rate of seedlings and learn to carbon and biomass distributions. This aims of the study is to know the level of carbon distribution of Manggis, Lengkeng, Sengon and Jelutung seedlings. The samples of selected seedlings were removed (destructive method). The roots washed by water to remove the sticky soil. The samples dried for 1 day, dried with a temperature of 102 ± 30C to constant weight. Samples that have dried out are separated by organs (roots, stems and leaves), to measure the weight of biomass. Method of calculating carbon by ash of biomass for calculating carbon percentages. The percentage of carbon multiplied by the calculation of biomass to calculate carbon. The results of the study show that the Lengkeng (14.10 g) seedlings have the higher value of carbon, than Manggis (5.14 g), Jelutung (3.80 g), Sengon (2.01 g), respectively. The distribution of carbon in seedling organs of the seedling level were varies. Jelutung and Lengkeng seedlings were higher value of carbon distribution in stem, than the roots, the leaves, respectively. Sengon seedlings have the larger value of carbon distribution in the leaves, than the stems and the roots, respectively. Manggis seedlings have the larger value of biomass distribution in stem than the leaves, the roots, respectively.